2014
DOI: 10.1093/ejcts/ezu127
|View full text |Cite
|
Sign up to set email alerts
|

National review of use of extracorporeal membrane oxygenation as respiratory support in thoracic surgery excluding lung transplantation

Abstract: VV or VA ECMO is a satisfactory alternative to in-field ventilation in complex tracheo-bronchial surgery or in single-lung surgery. ECMO should be considered and used in precarious postoperative respiratory conditions. Full respiratory support can be achieved with VV ECMO. Indications for and results of ECMO during surgery in patients with ARDS warrant further careful investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
65
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 24 publications
0
65
0
3
Order By: Relevance
“…17 This trial reported a significant improvement in the mortality rate without severe disability at six months in patients with severe respiratory disease who were transferred to a specialist centre for consideration for ECMO treatment compared with continued conventional ventilation. Since then, the use of either form of ECMO has been used for a wide range of conditions that require cardiac and/ or respiratory support, 16,18,19 as well as for support during a range of cardiac and thoracic 20 interventions.…”
Section: Guidelinesmentioning
confidence: 99%
“…17 This trial reported a significant improvement in the mortality rate without severe disability at six months in patients with severe respiratory disease who were transferred to a specialist centre for consideration for ECMO treatment compared with continued conventional ventilation. Since then, the use of either form of ECMO has been used for a wide range of conditions that require cardiac and/ or respiratory support, 16,18,19 as well as for support during a range of cardiac and thoracic 20 interventions.…”
Section: Guidelinesmentioning
confidence: 99%
“…Another alternative option described in human medicine is the use of cardiopulmonary bypass. 20 Unfortunately, the necessary equipment and trained personnel are rarely available in veterinary hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Local insertion-site infections (9.7% versus 17 -49%) and cannula-related bleeding requiring surgical revision or blood transfusions (2.8% versus 17%) are less frequently observed compared with conventional double-venous cannulation in VV-ECMO. 4,5,[8][9][10][11] A further, at least theoretical, advantage may be a de-escalation of inflammatory and thrombotic responses; this due to fewer plastic materials being directly inserted into the large veins of the human body. 4,8 Some authors criticize the Avalon ® system in terms of limited blood flow, which may be problematic, in particular, for taller hypoxemic patients.…”
Section: Discussionmentioning
confidence: 99%